(untitled) (Asian Journal of Medical and Biological Research, 2020)
The present research work was conducted to develop a balanced ration for crossbred high yielding calves in farm condition. For this purpose, seventy days long feeding trial was conducted with nine crossbred female calves having nearly similar body weight and age. Nine crossbred calves were equally divided into three groups such as T1 (1 kg concentrate mixture of crushed maize, wheat bran, mustard oil cake, molasses, DCP and salt at a ratio of 25:45:22:5:1:2, respectively), T2 (1 kg concentrate mixture of crushed maize, wheat bran, soybean cake, molasses, DCP and salt at a ratio of 27:45:20:5:1:2, respectively) and T3 (Wheat bran, rice polish, mustard oil cake, DCP, Salt were supplied according to BAU routine farm feeding at a ratio of 65:18:14:1:2, respectively). All calves were supplied with ad libitum green grasses (German and Para) and fresh clean drinking water. From the research finding, it was observed that the average total dry matter intake, total body weight gain, body length gain and heart girth gain were in T1 (2.68a±0.000 kg, 2.51a±0.21 kg, 1.83a±0.12 cm, 1.29a±0.07 cm, respectively) and T2 (2.65a±0.001 kg, 2.55a±0.21 kg, 1.67a±0.12 cm, 1.25a±0.07 cm, respectively) groups significantly (p<0.05) higher than that of the T3 (2.34b±0.002 kg, 0.96b±0.21 kg, 0.81b±0.12 cm, 0.64b±0.07 cm, respectively) group. The result showed that the body weight gain of T2 group was higher by supplementation of balanced ration. Therefore, the feed supplementation of crushed maize, wheat bran, soybean cake, molasses, DCP and salt at a ratio of 27:45:20:5:1:2, respectively should be supplied to crossbred calves for the future development of dairy herd replacement stock for profitable dairy business. Asian J. Med. Biol. Res. September 2020, 6(3): 499-506